Code Switching and Code Mixing in Denny Sumargo’s Podcast on Toxic Relationships - Karisma Tarigan; Yesika T. Girsang (UIN Salatiga, 2025)
This research explores the sorts of code-switching and code-mixing in a conversational podcast episode on toxic relationships based on their patterns and pragmatic uses. In this research, the linguistic data were evaluated qualitatively from the podcast episode using content analysis, guided by Speech Act Theory (Austin, 1962; Searle, 1969) and Relevance Theory (Wilson & Sperber, 2004) to examine how language alternation supports communicative and pragmatic functions. Five forms of code-switching were identified: inter-sentential, intra-sentential, tag-switching, situational Switching, and metaphorical Switching, along with three types of code-mixing: insertional, alternational, and congruent lexicalization. It explores how these tactics are deployed intentionally: to frame the narrative, explain intricately, heighten emotional resonance, and address a bilingual audience. The results reveal that code-switching differentiates between universal concepts and culturally bound situations, while code-mixing fills lexical gaps and allows conversational authenticity. These tactics underline speakers' ability to balance global accessibility with cultural relevance in effective and relatable content. This research introduces the theory of Bilingual Narrative Pragmatics, which says that bilingual speakers employ language alternation as a strategic tool to enhance narrative efficiency and audience appeal in digital and conversational media.